Optimal Path Planning for Mobile Robot Using Tailored Genetic Algorithm - Fei Liu; Shan Liang; Dong Xiao Xian (Institute of Advanced Engineering and Science, 2014)
During routine inspecting, mobile robot may be requested to visit multiple locations to execute special tasks occasionally. This study aims at optimal path planning for multiple goals visiting task based on tailored genetic algorithm. The proposed algorithm will generate an optimal path that has the least idle time, which is proven to be more effective on evaluating a path in our previous work. In proposed algorithm, customized chromosome representing a path and genetic operators including repair and cut are developed and implemented. Afterwards, simulations are carried out to verify the effectiveness and applicability. Finally, analysis of simulation results is conducted and future work is addressed.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3127